Clinical Manifestation and Laboratory Finding of Sclerosis Systemic Patient in Dr. Hasan Sadikin General Hospital Bandung : A Descriptive Quantitative Study - Annisa Meivira Budiman; Sumartini Dewi; Marietta Shanti Prananta (Indonesian Rheumatology Association, 2018)
Background Systemic sclerosis is a chronic progressive multisystem autoimmune disease in connective tissue, characterized by its heterogeneous clinical manifestation. The purpose of this study is to give information regarding clinical manifestations and laboratory findings of systemic sclerosis patients to establish diagnosis of disease. Methods This study was conducted using descriptive quantitative design in September−October 2016. Data was collected from medical records of patients visiting Rheumatology Clinic Dr. Hasan Sadikin General Hospital from 1 July 2015−30 June 2016 using total sampling method. The collected data were expected to comprise patient’s clinical manifestation and laboratory finding. Results Most of patients had cutaneous 57 (100.0%) and musculoskeletal 40 (70.2%) involvement. Some of the disease manifestations were Raynaud’s phenomenon 38 (66.7%), fingertip lesion 33 (57.9%), stiffness in skin 34 (59.6%), and arthalgia 29 (50.9%). Gastrointestinal involvements were present in 29 (50.9%) patients. Renal involvement were determined from urinalysis result showed proteinuria 10 (17.5%) and hematuria 8 (14.0%), found in 24 (42.1%) patients, while pulmonary and cardiac involvements were found in 30 (52.6%) patients, acknowledged from clinical symptoms such as dyspnea 12 (21.1%). Identification of autoantibodies was found in 12 (21.1%) patients, with 10 (17.5%) patients had reactive ANA and 3 (3.5%) had positive anti-Scl70. Conclusion Most of systemic sclerosis patients had cutaneous involvement. Renal, pulmonary, and cardiac involvement were concluded based on laboratory findings. Keywords: Systemic sclerosis, clinical manifestation, laboratory finding